THE SOURCES OF ONTOLOGICAL THOUGHT IN THE WORKS OF IVAN FOCHT - Berislav Njegovec (Hum, 2013)
Fundament of Ivan Focht’s ontology is an effort to think about what the work of art in a time of tehnocracy and domination of reason is. Focht continues phenomenolgical thought written in works of Husserl, Ingarden, Hartmann, Adorno, giving his contribution in further understanding of art work’s layered architecture. Today, twenty years after his death, the question abuout the work of art’s essence still stands and calls for debate. It is necessary to examine influence of above mentioned authors on Focht to gain insight on wider context around his current questions, and his conception of art as a compensation of dehumanizated and artificial world, trying to use the sensory field in reaching the area of genuine human spirit. Work of art is fundamented in it’s own being, which gives it ontological capability and conducts spirit from possibility to reality.